Two compounds with trans-[Mo(NCS)4(y-pic)2]– anion - Kitanovski, Nives (Array, 2009)
Summary: By refluxing a mixture of (NH4)2[MoCl5(H2O)] and KSCN in γ-picoline, crystalline trans-[(γ-pic)2H][Mo(NCS)4(γ-pic)2] (1) was prepared. After addition of P(C6H5)4Br to the solution of 1 in acetonitrile, trans-[P(C6H5)4][Mo(NCS)4(γ-pic)2]·2CH3CN (2) was isolated. Both compounds were characterized by IR spectroscopy, and their crystal structures were determined. X-ray structural analysis revealed the presence of trans-[Mo(NCS)4(γ-pic)2]– anions, with N-bonding of the NCS groups in both compounds. The positions of the ν(CN) and δ(NCS) bands are in agreement with the crystal-structure results. The results of analyses were compared with the results of the related trans-(py2H)[Mo(NCY)4py2] (Y = S,O) complexes